PENGARUH MEDIA DAN KONSENTRASI BAP TERHADAP PERTUMBUHAN TUNAS MIKRO PISANG RAJA SECARA IN VITRO (The Influences of Media and BAP Concentrations on Raja Banana Microshoots Growth In Vitro) - Lucky Prayoga (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2009)
A research of the influence of media and BAP concentrations on raja banana micro shoots growth has been carried out from November 2005 until July 2006. During the research, a split plot design has been used. The main plot was the kind of media; i.e. MS and Gamborg. The sub plot was BAP concentrations (K); i.e. K0: 0 .M, K1: 5 .M, K2: 10 .M, K3: 15 .M, K4: 20 .M and K5: 25 .M. On the plantlet formation, a factorial treatment pattern on CRD has been used. The result showed that both MS and Gamborg media could be used in planting raja banana micro shoots. The best growth of the micro shoots appeared with the addition of 15 .M BAP into the media. Key words : Raja banana, culture media, BAP.